New methylene blue analogues with N-piperidinyl-carbinol units: Synthesis, optical properties and in vitro internalization in human ovarian cancer cells. (September 2022) - Stoean, Bianca; Gaina, Luiza; Cristea, Castelia; Silaghi-Dumitrescu, Radu; Branzanic, Adrian M.V.; Focsan, Monica; Fischer-Fodor, Eva; Tigu, Bogdan; Moldovan, Cristian; Cecan, Andra Diana; Achimas-Cadariu, Patriciu; Astilean, Simion; et al.
Abstract: In this work, two new phenothiazinium dyes containing N -piperidinyl-carbinol auxochrome units have been designed, synthesized and investigated in vitro for ovarian cancer cell fluorescence imaging and cytotoxicity. A solvent free mechanochemical procedure is described as a greener alternative to the previously reported synthetic methodology applied in the preparation of methylene blue analogues by the substitution of the phenothiazinium tetraiodide substrate with nucleophilic secondary amines in solution. The optical properties of the new dyes were evaluated by UV–vis absorption/emission spectroscopy which revealed maxima situated in the red region (λmax absorption = 668-664 nm and λmax emission = 715-698 nm) with large molar extinction coefficients (log  ε  = 4.5–5.1) and bathochromic shifts of 314–383 cm −1 occurring upon switching from less polar to more polar solvents. The theoretical DFT computational study performed in order to clarify the obtained data indicated that the vertical TD-DFT calculations (typically applied for simulating UV–vis spectra) were within ∼150 nm of the experimental data, but a better agreement with experiment was obtained by using the vibronic corrections which revealed a dominant vibronic component not only for the main absorption/emission maxima, but also for the displayed shoulders which are rather the effects of the vibronic coupling between S0 and S1 electronic states. The new dyes presented a hydrophilic character (logP n -octanol/water  = −1.15 and −1.29 respectively) comparable to the parent methylene blue and no aggregation tendency was observed in aqueous solution at concentration range 75–150 μM used in this study. Cellular imaging experiments displayed the new dyes' ability to selectively stain the cytoplasm of tumoral OVCAR-3 and A2780 fixed cells. The evaluation of their biological activity encompassed cell grow inhibitory potential (dose-response activity and half maximal inhibitory concentration IC50 ), as well as their capacity to influence the tumoral OVCAR-3, A2780 and healthy BJ ovarian cells' metabolic activity. Dye 2 exhibited moderate cytotoxicity against human ovarian cancer cell lines, being the most active against the A2780 ovarian adenocarcinoma cells where its cellular uptake was noteworthy and displayed a deeper influence on the chemoresistant, highly malignant OVCAR-3 cells function by modulating FOLR1, ICAM-1 and VCAM-1 proteins with role in the growth and migration of cancer cells. Graphical abstract: Image 1 Highlights: New symmetrical Phenothiazinium dyes containing N-piperidinyl-carbinol auxochrome. Solvent free mechanochemical procedure for the synthesis of MB analogues. Optical properties enlightened by theoretical TD-DFT calculations with vibronic correction. In vitro cytoplasmatic accumulation and staining of ovarian tumor cell lines. Cytotoxicity and multitarget influence on ovarian tumor cell's functions.